Hemispheric and Transborder Perspectives: Racialization of Mexicans through Time (Konturen, 2013)
This article embeds a discussion of contemporary transborder communities—communities spread out in multiple locations in the U.S. and Mexico—in the history of U.S.-Mexico relations as seen through the colonial and contemporary mapping of space, place, people, race, and ethnicity both visually through the creation of maps and then metaphorically through U.S. immigration policy in the 19th and 20th centuries. I argue that the concept of “transborder” which can include borders of coloniality, ethnicity, race, nation, and region can help us to illuminate U.S.-Mexico relationships through time and the complexities of the racialization of Mexicans in the U.S.